Arterial access for cardiac procedures. (July 2022) - Ezad, Saad; Rawlins, John
Abstract: Obtaining safe arterial access is a prerequisite for any catheterization procedure, with radial access now the predominant access site for coronary intervention. Owing to the superficial nature of the radial artery, major complications relating to cannulation occur less frequently and are simpler to manage. However, because of an increase in the need for large-bore access to undertake structural intervention or insert mechanical circulatory support devices, the maintenance and improvement of femoral access skills remains crucial. Furthermore, safe and effective closure of a large-bore arteriotomy is essential, with an increasing number of devices available to facilitate this. Although the use of alternate access sites such as the axillary artery is growing, particularly for structural procedures, radial and femoral access remain the cornerstones of access sites for cardiac catheterization.